Dante's virtù: Creation, Embodiment, and Revelation. (February 2015) - Chester, Ruth
Abstract : This article addresses Dante's use of the term virtù in the Commedia and argues for its relevance as a key issue for exploring the poet's thinking on metaphysics, theology, ethics and the human body. Against the backdrop of a more richly contextualized idea of virtue in medieval thought, literary analysis of certain key passages of the Purgatorio and Paradiso throws new light on the way Dante explores the role of human existence in understanding the universe and working towards salvation.